(untitled) (Research, Society and Development, 2021)
This work aims to present a methodology for the synthesis and characterization of iron oxide nanoparticles as a tool to teach scientific concepts about nanomaterials for higher education. The justification for the inclusion of such experimental activity in practical chemistry classes is due to the revolution that has been taking place in the development of materials and devices on a nanometric scale and in its vast field of application. More specifically, magnetic nanoparticles are important in several areas, as they have potential for improvement in production technologies, electronic materials, in the telecommunications sector, in biomedicine, in the remediation of the environment, among others. Using inputs with a low level of toxicity, easy access and low cost, the proposed methodology uses easy-to-handle techniques to obtain nanoparticles, as well as accessible tests for characterization. As a result, it is expected that the insertion of this activity will allow the discussion of scientific, technological and social concepts related to nanomaterials, as well as the understanding of the precipitation method for the synthesis of nanoparticles, and of the analytical tests for characterization. It is expected that this activity will promote the introduction of basic concepts of nanoscience and nanotechnology, which are present in the contemporary world, and which should be brought to the classroom.